Модуляционная поляриметрия полного внутреннего отражения, нарушенного алмазоподобными пленками - Maximenko, L. S.; Mishchuk, O. N.; Matyash, I. E.; Serdega, B. K.; Kostin, E. G.; Polozov, B. P.; Fedorovich, O. A.; Savinkov, G. K. (PE "Politekhperiodika", Book and Journal Publishers, 2013)
This article presents research results on diamond-like films produced under different technological conditions. The parameter ρ — polarization difference — has been introduced. It has been found from spectral features of the parameter ρ that the interaction of electromagnetic radiation with the electronic system of specimens, which occurs in the used spectral range, consists of local and polariton surface resonances, differing in frequencies and times of relaxations. The authors concluded that the correlation in resonance intensity is defined by the structural characteristics of the specimens. These results show that modulation polarimetry is a perspective technique for diagnostics of the structural homogeneity of composite nanocluster films.